Nghiên cứu ảnh hưởng của hàm lượng chất tạo xốp, chất xúc tác và phụ gia đến khả năng cách âm và chống cháy của xốp PU. - Thuỷ, Nguyễn Thị Bích (Vietnam Journal of Chemistry, 2012)
In this research, the effect of blowing agents and catalysis on foam properties was examined. According to our findings, the sample C with 7%, 0.8%, 0.09% of blowing agent, ammine and zinc catalysis respectively showed the best mechanical strength, acoustics, and thermal insulation capabilities. We suggest that this finding is appropriate for acoustic and thermal insulation material production, especially in manufacturing of transport vehicles.